Development of ssDNA Aptamers for the Sensitive Detection of Salmonella typhimurium and Salmonella enteritidis - Park, Hae-Chul; Baig, Irshad Ahmed; Lee, Sang-Choon; Moon, Ji-Young; Yoon, Moon-Young (Applied biochemistry and biotechnology, 2014)
Salmonella enterica subsp. enterica ser. enteritidis and Salmonella enterica subsp. enterica ser. typhimurium are the most common and severe food-borne pathogens responsible for causing salmonellosis in humans and animals. The development of an early and ultra-sensitive detection system is the first critical step in controlling this disease. To accomplish this, we used the cell systematic evolution of ligands by exponential enrichment (Cell-SELEX) technique to identify single-stranded DNA (ssDNA) aptamers to be used as detection probes that can specifically bind to S. enteritidis and S. typhimurium. A total of 12 target-specific ssDNA aptamers were obtained through ten rounds of Cell-SELEX under stringent selection conditions, and negative selection further enhanced the selectivity among these aptamers. Aptamer specificity was investigated using the gram-negative bacteria E. coli and P. aeruginosa and was found to be much higher towards S. enteritidis and S. typhimurium. Importantly, three candidate aptamers demonstrated higher binding affinities and the dissociation constants (Kd) were found to be in the range of nanomolar to submicromolar levels. Furthermore, individual aptamers were conjugated onto polyvalent directed aptamer polymer, which led to 100-fold increase in binding affinity compared to the individual aptamers alone. Taken together, this study reports the identification of higher affinity and specificity ssDNA aptamers (30mer), which may be useful as capture and detection probes in biosensor-based detection systems for salmonellosis.